2013
DOI: 10.3389/fnhum.2013.00261
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among cognition, emotion, and motivation: implications for intervention and neuroplasticity in psychopathology

Abstract: Emotion-cognition and motivation-cognition relationships and related brain mechanisms are receiving increasing attention in the clinical research literature as a means of understanding diverse types of psychopathology and improving biological and psychological treatments. This paper reviews and integrates some of the growing evidence for cognitive biases and deficits in depression and anxiety, how these disruptions interact with emotional and motivational processes, and what brain mechanisms appear to be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 277 publications
(391 reference statements)
3
82
0
2
Order By: Relevance
“…However, it might be hypothesized that additional constructs, such as executive inflexibility (e.g., impairment in shifting, for review see Snyder et al, 2014), are important components of anxious apprehension. Such a conceptualization might posit that a breakdown in executive flexibility interacting with a rise in negatively-valenced/high-arousal affect sustains a pattern of negative, repetitive thinking (see Crocker et al, 2013;Gotlib and Joormann, 2010) leading to a persistent pattern that constitutes anxious apprehension. This conceptualization borrows from psychological constructionist theory (e.g., Russell, 2003), which posits that basic 1 Fear has been distinguished from anxiety (Davis et al, 2010;Hofmann, Ellard and Siegle, 2012).…”
Section: State Vs Trait Anxietymentioning
confidence: 98%
See 1 more Smart Citation
“…However, it might be hypothesized that additional constructs, such as executive inflexibility (e.g., impairment in shifting, for review see Snyder et al, 2014), are important components of anxious apprehension. Such a conceptualization might posit that a breakdown in executive flexibility interacting with a rise in negatively-valenced/high-arousal affect sustains a pattern of negative, repetitive thinking (see Crocker et al, 2013;Gotlib and Joormann, 2010) leading to a persistent pattern that constitutes anxious apprehension. This conceptualization borrows from psychological constructionist theory (e.g., Russell, 2003), which posits that basic 1 Fear has been distinguished from anxiety (Davis et al, 2010;Hofmann, Ellard and Siegle, 2012).…”
Section: State Vs Trait Anxietymentioning
confidence: 98%
“…As evidence from clinical neuroscience and psychology has accumulated regarding the interactions among executive functions and dimensions of anxiety (e.g., Crocker et al, 2013;Levin et al, 2007;Snyder et al, 2014), it has become clear that deficits in executive function capacities can be predisposing risk factors, maintaining components, and/or negative consequences of anxiety disorders. Executive function is a broad term encompassing many cognitive processes, which in general coordinate behavior adaptively toward a goal (Banich, 2009).…”
Section: Executive Function Impairmentsmentioning
confidence: 99%
“…Numerous theoretical models (see Banich et al, 2009;Crocker et al, 2013;Groman, James, & Jentsch, 2009) and empirical demonstrations (e.g., Fillmore & Rush, 2006;Mezzacappa, Kindlon, & Earls, 1999;Romer et al, 2009;Shehzad, DeYoung, Kang, Grigorenko, & Gray, 2012) have underscored the role of cognitive control and its neural correlates in externalizing psychopathology. Specifically, dysfunction in frontal and prefrontal cortical circuits known to underlie cognitive control abilities, such as inhibition, attention control, and planning, are characteristic of individuals who exhibit externalizing problems such as impulsive aggression (e.g., Giancola, 1995;Giancola & Zeichner, 1994), attention-deficit disorder (e.g., Aron & Poldrack, 2005;Itami & Uno, 2002), drug abuse (e.g., Thompson et al, 2004), and risky sexual activity (Miner, Raymond, Mueller, Lloyd, & Lim, 2009).…”
Section: Cognitive Control and Its Impairment By Alcoholmentioning
confidence: 99%
“…Beauchaine (2001) hypothesized that high levels of BA involves high levels of physiological arousal, which could also heighten risk for anxious arousal. Consistent with this idea, hypersensitivity to rewards and physiological activation in the context of reward processing are associated with anxiety (Crocker et al 2013), and one study found that BA was associated with heightened symptoms of anxious arousal and anxious apprehension in emerging adults (Spielberg et al 2011). BA is thought to instigate impulsive behavior, which may help to explain why those with high BA are at heightened risk for externalizing problems such as substance use (Johnson et al 2003) and manic symptoms of Bipolar disorders (Fletcher et al 2013;Johnson et al 2012).…”
Section: Behavioral Inhibition and Behavioral Activationmentioning
confidence: 89%